PENURUNAN KANDUNGAN BOD DAN COD LIMBAH CAIR KELAPA SAWIT MENGGUNAKAN METODE ELEKTROKOAGULASI - Masthura Masthura; Abdul Halim Daulay; Lansari Daulay (UIN Sumatera Utara Medan, 2021)
Research using the electrocoagulation method has been carried out to determine the results of the sample test results for BOD and COD parameters in palm oil mill effluent. The electrodes used n this method are aluminium electrodes with varying adapter voltages of 6, 9, and 12 Volts. Palm oil liquid waste used comes from PTPN IV Adolina Perbaungan. The results of the study showed that before the electrocoagulation method the BOD value obtained was 243 mg/l, while after the electrocoagulation method the best results were obtained at a voltage of 12 Volt with a value of 52,5 mg/l. The value obtained before the electorocoagulation method was carried out on the COD parameter was 649 mg/l and after the electrocoagulation method the best results were obtained at a voltage of 12 Volt, which was 110 mg/l. This shows that the parameter values of BOD and COD in processed waste have decreased and meet the wastewater quality standards for the palm oil industry, namelyb 100 mg/l and 350 mg/l. The higher the value of the applied voltage, the more optimal the levels of BOD and COD.